Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/sap.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Permanent Implant Reconstruction Following Mastectomy With Capsule Preservation in Patients With Prior Augmentation Mammoplasty

Abstract: Prior breast augmentation in patients desiring post-mastectomy reconstruction provides a unique opportunity for capsular preservation and immediate, single-step implant reconstruction. We report a case series of a single-surgeon experience with immediate implant reconstruction after skin-sparing mastectomy in patients with prior subpectoral augmentation. Final implant volumes, complications, and outcomes were examined. Twenty patients (15 bilateral, total 35 breasts) were included. Eighteen (90%) patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Consistent with previously published studies, 8–11 our findings demonstrate that despite the variability in operative techniques, immediate implant-based breast reconstruction in patients who have undergone previous augmentation is as safe as in the remainder of the cohort. The thinner skin flaps, which may be attributable both to the lower body mass index of the augmented cohort and to the subcutaneous thinning secondary to the presence of the implant, may be balanced by the prior breast augmentation serving as a delay procedure and increasing the vascularity of the skin envelope by expansion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previously published studies, 8–11 our findings demonstrate that despite the variability in operative techniques, immediate implant-based breast reconstruction in patients who have undergone previous augmentation is as safe as in the remainder of the cohort. The thinner skin flaps, which may be attributable both to the lower body mass index of the augmented cohort and to the subcutaneous thinning secondary to the presence of the implant, may be balanced by the prior breast augmentation serving as a delay procedure and increasing the vascularity of the skin envelope by expansion.…”
Section: Discussionsupporting
confidence: 91%
“…Standard staged reconstruction with a tissue expander followed by a permanent implant can be performed, 6 but immediate reconstruction with a fixed volume implant, often facilitated by the use of biological or synthetic mesh, is the most common procedure reported in the European literature. 7 Studies of implant-based reconstruction following augmentation, however, have reported conflicting findings, with some authors reporting an acceptable safety profile, [8][9][10][11] whereas others highlighted an increased risk of complications in this group of patients. 6,12 These studies, however, were mostly small, and all were single center and at high risk of bias.…”
mentioning
confidence: 99%
“…9 Superior implant malposition and resulting breast asymmetry is more frequent following breast augmentation associated with simultaneous breast lift procedure. 10,11 This is likely due to tightening of the lower breast pole skin as part of the lift procedure. Similarly, the incidence of superior breast implant malposition following breast reconstruction is more commonly observed likely secondary to the more aggressive removal of the lower breast pole skin and soft tissues during, for example, a mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study of 20 patients, they found good aesthetic outcomes, appropriate complication rates, and no cancer recurrences. 5 Although these initial studies suggest ISM to be a surgical technique with good aesthetic outcomes, possibly lower complication rates, and acceptable local recurrence rates, further evaluation with a focus on oncologic outcomes, surgical complications, and reconstruction patterns was warranted. As such, we aimed to study the oncologic outcomes, 90-day surgical complication rates, and factors associated with complications, as well as the patterns of reconstruction for patients receiving ISM at our institution from 2006 to 2018.…”
Section: Introductionmentioning
confidence: 99%